A Systematic Review on the Efficacy of Topical Acyclovir, Penciclovir, and Docosanol for the Treatment of Herpes Simplex Labialis - Kimberly D.P. Hammer; Jessica Dietz; Tze Shien Lo; Erika M. Johnson (European Medical Journal, 2018)
Background: Herpes simplex labialis is a common skin condition caused by the herpes simplex virus. The prescription of antivirals for the treatment of herpes labialis is common. The objective of this study was to conduct a systematic review of the available evidence on the treatment of herpes simplex labialis with U.S. Food and Drug Administration (FDA)-approved topical antibiotics. Methods: The literature search included searches of PubMed, Google Scholar, and Scopus. This review included studies that examined herpes labialis lesions and treatment with topical acyclovir, penciclovir, or docosanol in at least one of the study arms. Results: Of the 1,485 papers initially identified, 20 papers representing 19 randomised controlled trials and one quasi-randomised trial met the inclusion criteria for the systematic review. Conclusion: Our systematic review of the clinical studies performed on the three topical antiherpetics, acyclovir, penciclovir, and docosanol, showed that their efficacy compared to placebo is marginal at best (shortening the duration of pain by <24 hours), although the three topical antiherpetic drugs have no serious adverse reactions and are safe to use.